Effects of weld geometry and HAZ property on low-cycle fatigue behavior of welded joint. (March 2022) - Tsutsumi, Seiichiro; Fincato, Riccardo; Luo, Pengjun; Sano, Moe; Umeda, Toshihiro; Kinoshita, Tomohiro; Tagawa, Tetsuya
Highlights: Low-cycle fatigue performance of welded joints. Effect of the weld toe profile and material heterogeneity. Description of inelastic deformation through cycles. Characterized the mechanical properties of base metal and HAZ. DIC characterization of strain distribution. Validation against experimental data. Abstract: A previous experimental study by the authors clearly indicated that, due to the delay of the crack initiation, the butt-welded joint with smoother weld toe profile and harder weld metal had a longer low-cycle fatigue life. In the present study, supplementary numerical studies considering weld geometries and inhomogeneous mechanical properties are executed. Monotonic tensile and strain-controlled low-cycle fatigue tests on the reheated round bars are firstly conducted to characterize the mechanical properties for different zones of the butt-welded joints. The test results are used to calibrate the material constitutive model, which is then embedded into three-dimensional finite element models to investigate the low-cycle fatigue behavior of the butt-welded joints. The numerical results suggest the necessity of considering the effects of inhomogeneous material properties when evaluating the low-cycle fatigue of welded joints. It is also confirmed that decreasing weld toe stress concentration and simultaneously increasing weld metal strength can maximally increase the low-cycle fatigue life of welded joints compared to the individual changes for either one. These findings are expected to provide some insights into the low-cycle fatigue life improvement of welded joints.